(untitled) (Communications in Computational Physics, 2006)
This paper is concerned with the adaptive grid method for computations of the Euler equations in fluid dynamics. The new feature of the present moving mesh algorithm is the use of a dimensional-splitting type monitor function, which is to increase grid concentration in regions containing shock waves and contact discontinuities or their interactions. Several two–dimensional flow problems are computed to demonstrate the effectiveness of the present adaptive grid algorithm.